PENERJEMAH, PENERJEMAHAN, TERJEMAHAN, DAN DINAMIKA BUDAYA: MENATAP PERAN PENERJEMAHAN PADA MASA LALU DI NUSANTARA - Benny H. Hoed (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2011)
This paper describes the role and impact of translation on cultural change.Translation is defned as an effort to divert messages from one language(source language) into another language (target language). Language, throughtranslation and transfer of messages, can affect the formation of the targetculture as stated in the Sapir-Whorf hypothesis. Many studies on translationare generally talking about the quality of translation. This paper however doesnot discuss about quality of the translation instead it focuses on the role oftranslation and its impact on target communities. Specifcally, it talks aboutthe subject of the translation and the translation in the beginning of Hinduismand Islamic period and the New Order period in Indonesia.The paper observes the translation from the perspective of its purpose,which is known as skopos method. It reviews four articles contained in thebook ofSadur. The paper also shows how the translation may have an impacton cultural change, i.e. how the translators introduce, distribute, or takeadvantage of cultural elements contained in the source text while adjustingto the needs of target communities. The main purpose of those translationsstudied is to spread the religion, literature, and social rules. There are threethings observed through translation: (i) the role of the source language as thelanguage of religion, administration, and literature is taken over by the targetlanguage. (ii) the genre of the source language is replaced with the genre ofthe target language. (iii) teaching of Hinduism and Islam were inserted intolocal religious teachings; literary sources adapted to local literature. The paperconcludes that the Sapir-Whorf hypothesis applies where the translationshapes culture. And translation, based on the principle of sadur (adaptation)and pemribumian (domestication), has formed a new fgure of localculture in the history of Indonesia.Keywords: cultural change, translation